Effect of Molecular Structure and Coordinating Ions on the Solubility and Electrochemical Behavior of Quinone Derivatives for Aqueous Redox Flow Batteries. Issue 16 (20th November 2020) - Huang, Zhifeng; Lee, Jongwook; Henkensmeier, Dirk; Hempelmann, Rolf; Kim, Sangwon; Chen, Ruiyong
Abstract : Water soluble organic redox-species have been studied in redox flow batteries as promising alternatives to overcome the limitation of current vanadium chemistry such as low energy density and high cost. Herein, a comparative physicochemical and electrochemical study of several structurally similar quinones in different molalities of imidazolium-based aqueous electrolytes highlights the importance of the molecular structure of organic solutes and their coordination with the imidazolium cations in electrolytes. A quinone derivative of 2-methoxyl-hydroquinone with a record solubility of 7.9 M at room temperature is obtained in the aqueous imidazolium-based supporting electrolyte. This is close to a maximum value of 8.13 M in its molten state, suggesting a new approach to dissolving organic-active materials. In addition, strong coordination imposes a significant effect on the chemical/electrochemical stability and redox potential of the organic quinones. The reaction kinetics and cycling performance of the 2-methoxyl-hydroquinone as catholyte in a redox flow battery have been investigated by pairing it with a vanadium anolyte (V 3+ /V 2+ redox pair), showing a high cycling efficiency and structural stability.